Sistem Pendukung Keputusan Untuk Pemilihan Tempat Wisata Pantai Berbasis Webgis Di Kabupaten Lampung Selatan - Zusan, Ulfah Atikah; Mayaguezz, Henky; Damai, Abdullah Aman; Effendi, Nur; Darmawan, Arief; Febryano, Indra Gumay (Journal of Tropical Marine Science, 2024)
In beach tourism development, the decision-making process via the web is a valuable tool that can provide several alternatives for decision-making planners in beach tourism development. The aim of this research is to develop the implementation of a decision support system for selecting WebGIS-based beach tourist attractions in South Lampung Regency. This research is research with the concept of Research and Development, the data used in this research is primary data obtained from field observations and secondary data obtained from the government. Data was obtained through observation and documentation studies from 30 beaches in South Lampung Regency, then processed using the Simple Additive Weighting method. The research results show that bio-physical and managerial factors are the factors that have the most influence on the results of this weighting and are the most dominant supporting alternatives for selecting beach tourist attractions in South Lampung Regency. The recommended beach tourism in South Lampung based on the highest weighting value is Pasir Putih Beach which is the highest ranked, followed by Tapak Kera Beach. Supporting factors such as bio-physical factors, socio-economic factors and managerial factors can be used as primary considerations for beach tourism managers and local governments should continue to develop and innovate in using Simple Addivite Weigting, because the method is much more practical and effective in determining object recommendations beach tourism for tourists.